Positioning the Beef Industry for the Future - Schroeder, Ted C.; Mintert, James; Brester, Gary W. (My University, 1995)
This publication describes issues and outlines strategies the beef industry may wish to consider when positioning itself.
MF2123_1995_05
Keywords: MF2123; Livestock; Economics; MF